Nonsense for old and young - Field, Eugene, 1850-1895; Frohn, John C. (Salt Lake City, UT : Project Gutenberg, 2024)
"Nonsense for Old and Young" by Eugene Field is a whimsical collection of humorous poetry and light-hearted prose, likely penned in the late 19th century. The book showcases Field's playful style, where he employs absurdity and satire to entertain both children and adults, suggesting that laughter and nonsense can be enjoyed at any age. The content is a diverse assortment of short verses, illustrations, and comical narratives, each designed to elicit laughter through clever wordplay and engaging characters. For example, Field presents a tale of "Good James and Naughty Reginald," contrasting the merits of good behavior against the mischievous antics of Reginald, while the imaginations of various whimsical figures illuminate the playful absurdity of life. With quirky observations on society, nature, and childhood antics, this collection invites readers into a delightful world where humor prevails amidst everyday situations. (This is an automatically generated summary.)
Release date is 2024-01-30
Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: American wit and humor; Humorous poetry, American